2022
DOI: 10.48550/arxiv.2201.07727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating the architecture and internal structure of the TOI-561 system planets with CHEOPS, HARPS-N and TESS

G. Lacedelli,
T. G. Wilson,
L. Malavolta
et al.

Abstract: We present a precise characterization of the TOI-561 planetary system obtained by combining previously published data with TESS and CHEOPS photometry, and a new set of 62 HARPS-N radial velocities (RVs). Our joint analysis confirms the presence of four transiting planets, namely TOI-561 b (𝑃 = 0.45 d, 𝑅 = 1.42 R ⊕ , 𝑀 = 2.0 M ⊕ ), c (𝑃 = 10.78 d, 𝑅 = 2.91 R ⊕ , 𝑀 = 5.4 M ⊕ ), d (𝑃 = 25.7 d, 𝑅 = 2.82 R ⊕ , 𝑀 = 13.2 M ⊕ ) and e (𝑃 = 77 d, 𝑅 = 2.55 R ⊕ , 𝑀 = 12.6 R ⊕ ). Moreover, we identify an additi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 92 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…Our model is The LHS 1903 planetary system presented in detail in ref. [42], and more information can be found in the Methods and in previous studies [41,[43][44][45][46][47]. Our analysis shows that the H 2 /He gas mass fraction in the three innermost planets increases with orbital distance (see Extended Data Fig.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…Our model is The LHS 1903 planetary system presented in detail in ref. [42], and more information can be found in the Methods and in previous studies [41,[43][44][45][46][47]. Our analysis shows that the H 2 /He gas mass fraction in the three innermost planets increases with orbital distance (see Extended Data Fig.…”
supporting
confidence: 58%
“…• The eccentricities, e, for all planets were constrained with half-Gaussian zeromean priors following refs. [41,173] with the width determined by the eccentricity distribution of compact multi-planet systems [174], such as LHS 1903, justified by dynamical arguments.…”
Section: Joint Transit Photometry and Rv Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Most commonly, such long-period planets are often gas giants that form beyond the snowline of their system, and therefore represent an entirely different regime of both size and composition when compared to their close-in companions. For systems that instead contain ultra-short period (USP) members, such as TOI-561 (Weiss et al 2021, Lacedelli et al 2022, it has been shown that the USP planets are often markedly smaller than other members of the same system, and may have experienced a much more dynamically volatile formation history. (Winn et al 2018).…”
Section: All Planets Have Rv Mass Measurements With Frac-mentioning
confidence: 99%